Investigating the Origin of Seismic Swarms. (8th October 2013) - Govoni, Aladino; Passarelli, Luigi; Braun, Thomas; Maccaferri, Francesco; Moretti, Milena; Lucente, Francesco Pio; Rivalta, Eleonora; Cesca, Simone; Hainzl, Sebastian; Woith, Heiko; De Gori, Pasquale; Dahm, Torsten; et al.
Abstract : According to the U.S. Geological Survey's Earthquake Hazards Program, a seismic swarm is "a localized surge of earthquakes, with no one shock being conspicuously larger than all other shocks of the swarm. They might occur in a variety of geologic environments and are not known to be indicative of any change in the long‐term seismic risk of the region in which they occur" (http://vulcan.wr.usgs.gov/Glossary/Seismicity/description_earthquakes.html).